Digital Academic Supervision Transformation to Improve Teacher Efficacy and Performance at SMAN 1 Bagan Sinembah - Nurul Hardianti Hasibuan; Maya Novita Sari (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Digital transformation has changed the way principals conduct academic supervision and has created new opportunities for data-informed teacher development. This study examined the transformation of principal academic supervision in improving teacher efficacy and performance in the digital era at SMAN 1 Bagan Sinembah. A qualitative case study design was applied from February to May 2026. Data were collected through semi-structured interviews with the principal, vice principals, teachers, and a school supervisor, participatory observation of supervision activities, and documentation of supervision policies, instruments, and follow-up programs. The data were analyzed using the interactive model of reduction, display, and conclusion verification, while credibility was strengthened through source triangulation, technique triangulation, and member checking. The findings show that digital supervision was transformed through data-based planning, classroom observation using digital instruments, integrated performance evaluation, and individualized mentoring. This transformation strengthened teachers' confidence in managing instruction, increased their willingness to use learning technology, and improved lesson planning, classroom implementation, assessment practices, and reflective collaboration. The study concludes that digital academic supervision works effectively when technology use is accompanied by collaborative leadership, constructive feedback, and continuous professional support